No-till and nitrogen fertilizer reduction improve nitrogen translocation and productivity of spring wheat (Triticum aestivum L.) via promotion of plant transpiration - Tan, Yan; Chai, Qiang; Li, Guang; Hu, Falong; Yu, Aizhong; Zhao, Cai; Fan, Zhilong; Yin, Wen; Fan, Hong (Frontiers in Plant Science, 2022)
Excessive nitrogen (N) fertilizer has threatened survivability and sustainability of agriculture. Improving N productivity is promising to address the above issue. Therefore, the field experiment, which investigated effect of no-till and N fertilizer reduction on water use and N productivity of spring wheat (Triticum aestivum L.), was conducted at Wuwei experimental station in northwestern China. There were two tillage practices (conventional tillage, CT; and no-till with previous plastic film mulching, NT) and three N fertilizer rates (135 kg N ha-1, N1; 180 kg N ha-1, N2; and 225 kg N ha-1, N3). The results showed that NT lowered soil evaporation (SE) by 22.4%, while increased ratio of transpiration to evapotranspiration (T/ET) by 13.6%, compared with CT. In addition, NT improved total N accumulation by 11.5%, and enhanced N translocation quantity, rate, and contribution by a range of 6.2–23.3%. Ultimately, NT increased grain yield, N partial factor productivity, and N harvest index by 13.4%, 13.1%, and 26.0%, respectively. Overall, N1 increased SE (13.6%), but decreased T/ET (6.1%) compared to N3. While, N2 enhanced N translocation quantity, rate, and contribution by a range of 6.0–15.2%. With integration of NT, N2 achieved the same level of grain yield and N harvest index as N3, and promoted N partial factor productivity by 11.7%. The significant positive correlation of N translocation relative to T/ET and grain yield indicated that improving T/ET was essential for achieving higher N translocation. Hence, we concluded that no-till coupled with N fertilizer rate at 180 kg N ha-1 was a preferable management option to boost N productivity of spring wheat in arid areas.